2022
DOI: 10.1021/acsestwater.2c00475
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide Thin-Film Composite Janus Membranes Avoiding Direct Contact between Feed Liquid and Hydrophobic Pores for Excellent Wetting Resistance in Membrane Distillation

Abstract: Hydrophobic membranes are very susceptible to pore wetting when they contact the feed water containing surfactants or low-surface-tension liquids in membrane distillation (MD). Avoiding direct contact between feed water and hydrophobic membrane pores is a potential strategy to control membrane pore wetting. In this study, we successfully fabricated a polyamide thin-film composite (TFC) Janus membrane through interfacial polymerization, with a hydrophobic microporous membrane as the substrate. The fabricated TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous research has indicated that the effects of electrostatic repulsion and attraction are rendered negligible in salt solutions due to the shielding effect of high ionic strength. , Therefore, size exclusion emerges as the predominant mechanism for wetting resistance, enabling the GO-TU layer to exhibit a satisfactory performance (Figure c). Furthermore, the dense layer also exhibited potential resistance ability of scaling-induced wetting (Figure S13), suggesting great advantages in wetting resistance …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has indicated that the effects of electrostatic repulsion and attraction are rendered negligible in salt solutions due to the shielding effect of high ionic strength. , Therefore, size exclusion emerges as the predominant mechanism for wetting resistance, enabling the GO-TU layer to exhibit a satisfactory performance (Figure c). Furthermore, the dense layer also exhibited potential resistance ability of scaling-induced wetting (Figure S13), suggesting great advantages in wetting resistance …”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the dense layer also exhibited potential resistance ability of scaling-induced wetting (Figure S13), suggesting great advantages in wetting resistance. 28 In addition, a range of commonly used surfactants in the environment was investigated (Table S3), 45 and their molecular sizes were found to be larger than the nanochannel size of the GO-TU layer. It further supports the ability of the GO-TU/PVDF membrane to resist practical wetting scenarios.…”
Section: Wetting Resistance Of the Go-tu/pvdf Membranementioning
confidence: 99%
See 1 more Smart Citation